The ambiguity of Johan Heyns: Sitting at Bavinck’s left or right hand? - Conradie, Ernst M (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
Following some biographic introductory comments, the argument of this contribution proceeds in two steps. First, the distinction between Herman Bavinck’s left and right hand is clarified, amongst others with reference to the distinction between fides qua and fides quae, and illustrated with examples from the subsequent Reformed tradition. second, an analysis of Heyns’ own related theological choices is offered on this basis.